Nutritional Assessment of End-stage Kidney Disease Patients on Maintenance Hemodialysis in Damaturu, Northeastern Nigeria - ABDU, Alhaji; GONI, Baba WARU; ABDUL, Habu; ABDULLAHI, Usaini (African Journal of Nutrition and Dietetics, 2025)
Malnutrition is among the morbidities associated with poor health-related quality of life and decreased functional capacity in patients on Hemodialysis. Several factors, such as decreased food intake due to anorexia, dietary restrictions, combined to make these patients susceptible to malnutrition. This study aimed to assess the nutritional status of hemodialysis patients and to identify possible risk factors that may be amenable to intervention. A total of 55 patients on maintenance hemodialysis for more than 3 months were recruited after consenting. All patients were interviewed during one of the sessions of hemodialysis. Information on demographic features such as Age, gender, and ethnicity was recorded. Subjective global assessment (SGA) was used in this study to assess nutrition. A blood sample was collected for the determination of serum Albumin, Hemoglobin, calcium, and phosphate. Among the 55 patients enrolled in the study, 41 (74.5%) were males and 14 (25.5%) were females. The mean age of the study cohort was 49.89± 10.2 years. The overall SGA score revealed that 18 (32.7%), 23 (41.8%), and 14 (25.5%) of the patients had normal nutrition, mild/moderate malnutrition, and severe malnutrition, respectively. There is a significant negative correlation between malnutrition and Hemoglobin (rho=-0.423, P=0.001), Albumin (rho=-0.378, P=0.004), and a positive correlation with increasing Kt/V (rho=-0.529, P=0.007). Compared with well-nourished patients (N=18), malnourished patients (N=37) were significantly females (χ2 =5.5, P=0.02), had shorter duration on dialysis (21.7±16.2 vs 15.0±10.3 months, P=0.04), and had lower Kt/V (1.5±0.08 vs 1.7±0.18, P=0.007). This study shows a high prevalence of mild/moderate and severe malnutrition among patients on maintenance hemodialysis in our center.